PENENTUAN KAPASITAS VEKTORIAL Anopheles spp. DI DESA REJEKI KECAMATAN PALOLO KABUPATEN SIGI SULAWESI TENGAH - Yuyun Srikandi; M. Arie Wuryanto; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2015)
Malaria remains a public health problem public health problem in Sulawesi, especially in Rejeki Village, Palolo Subdistrict, Sigi District. Rejeki village was a high endemic area of malaria from 2009 until 2012. In 2013, there was no positive case malaria, but the environmental condision there were very approriate to malaria transmission. Recently, in Indonesia there was lack of data about vectorial status and host identification as Anopheles bloodmeal. This research aimed to determine the vectorial capacity value of Anopheles spp. This Study was descriptive obsevational analysis with cross sectional design. The sample was female Anopheles spp. that caught allnight from 06.00 pm up to 06.00 am, and the mosquitoes that caught at the rest time in early morning. The collection was held for 6 times start from April until September. The mosquitoes that collected in Rejeki village were An. barbirostris, An. nigerrimus, An. tesselatus, An. vagus, An. indifinitus, and An. umbrosus. The result showed the species which potency as malaria vector that An. barbirostris (0,001-0,003) and An. nigerrimus (0,001-0,058). The average age of An. barbirostris was 8,58-13,78 days and An. nigerrimus was 4,24-13,78 days. ELISA bloodmeals test resulted mosquitoes which consumed human bloodmeals are An. barbirostris and An. nigerrimus, include in anthropophilic and tend to endophagic. Integrated vector control method is recommended to be applied in effort to maintained low malaria endemicity. Cattle barrier was a good solution for the control of malaria.